PERLINDUNGAN ISLAM TERHADAP NON-MUSLIM STUDI SURAT JAMINAN RASULULLAH SAW KEPADA BIARA SANTA KATARINA - Arifinsyah, A; Datmi, Akbar Rasyidi; Adnir, Farid (Jurnal Ushuluddin, 2019)
Many people consider Islam as a radical religion, anarchist, terrorist and so on, this stigma becomes a turning point of the values of Islamic peace as a religion rahmatan lil'alamin. Islam is also tarnished, especially in the eyes of non-Muslims who later led to Islamophobia in the West and Europe so that for them Islam is synonymous with violence and terrorism. In fact, hundreds of years ago Islam once ruled the world with peace, justice and safety. How can the Messenger of Allah be assured of the Monastery of Saint Catherine so that they are safe, comfortable and live peacefully in the protection of Islamic authority. This study aims to determine the guarantee of the Messenger of Allah against non-Muslims of their basic rights in religious, national and state life. The method used is descriptive qualitative method, which is a research process with a methodology that investigates the Prophet's agreement to the Monastery of St. Catherine through a historical approach. Broadly speaking, there are three findings in this study; first there is an indication of the authenticity of the text of the guarantee letter of the Prophet to the Monastery of Saint Catherine. Second, the contents of the manuscript are in accordance with Islamic teachings and law. Third, the contents of the agreement guarantee the basic rights of non-Muslims in religious life, nation and state, and encourage a life of tolerance, harmony, avoiding hostility and mutual respect.